Agrarian Conflict Resolution in the Strategic Perspective of National Defense: The Case of Batin Baringin Sakai Customary Community - Raundoh Tul Jannah; Endro Legowo; Achmed Sukendro; Rizky Budi P. Sulton (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2022)
Abstract: The strategy formulation of the Riau Province Government in the Perspective of the National Defense is needed to deal with the conflict between the customary community of Batin Baringin Sakai and PT Arara Abadi. This agrarian conflict occurred due to overlapping rights over customary land management, which has not yet come to light. From 1996 until now, the conflict never finds a solution. The Riau Provincial Government must complete homework with effective and efficient strategic steps. This study will analyze the strategic actions that the government can take to resolve the conflict between the two parties by examining the concept of the government's strategy from the Strategic Perspective of The National Defense. The research method used is qualitative, with case studies and interviews. The results explain that the strategic steps taken have not been maximized. So that there is no draft conflict resolution strategy guidelines between the Customary Peoples of the Batin Baringin Sakai and PT Arara Abadi by the Provincial Government of Riau. Several measures which include means, ways, and ends according to the perspective of the right and directed the Riau Provincial Government can carry out National Defense Stages how to maximize mobilization and integrate resources optimally through a work program that is compiled and evaluated. In the final stage, conflict resolution can be achieved through a peace agreement and a sense of justice between the two disputing parties. Keywords: Agrarian conflicts, ends, means, ways